A Cross-Sectional Study on Knowledge and Attitudes about Sexual Harassment among Nursing Students - Dwi Shinta Lase; Windi Luvita Sari; Gabriell Aquera Putri; Joice Cathryne; Kinanthi Lebdawicaksaputri (Nursing Current: Jurnal Keperawatan, 2025)
Sexual harassment against women is a growing problem that remains unresolved globally. Sexual harassment can cause trauma and even depression in victims. It can lead to psychological trauma and even depression in victims. Based on an initial survey of 20 female nursing students, 85% reported experiencing sexual harassment through words, stares, and whistles. Nurses are one of the health workers who are vulnerable to sexual harassment. The purpose of this study is to investigate the relationship between knowledge and attitudes of nursing students toward sexual harassment. This study employs univariate and bivariate analysis, using a quantitative correlational approach with a cross-sectional design, and the statistical test used is the chi-square test. The sample in this study consists of 199 first-year nursing students selected using purposive sampling. The study was conducted from January to March 2024. The results showed that 147 (73.9%) nursing students had good knowledge and 108 (54.3%) had a positive attitude toward sexual harassment, with a p-value of 0.014, indicating a significant relationship between knowledge and attitude toward sexual harassment. Good knowledge shapes students' attitudes toward sexual harassment. Students must continue to improve their knowledge about sexual harassment. Further research is encouraged to explore factors related to attitudes toward sexual harassment.